THE INFLUENCE OF PRODUCT QUALITY, PRICE, LOCATION ON PURCHASE DECISIONS AND PURPOSE OF PURCHASE OF SOUVENIR PRODUCTS IN SIKKA REGENCY, NTT - Yohana Anggriani; Djoko Koestiono; Dwi Retno Andriani (Socio-Economics/Agribusiness Department, 2022)
Consumer satisfaction with the product will be formed when someone makes a purchase decision. Perceived satisfaction will provide benefits for the company continuously. This means that everything related to the product received by consumers at the time of purchase will determine the direction of the company's goals. This research was conducted at Aku Sikka's ole shop in Sikka Regency, East Nusa Tenggara Province from May to June 2021. The purpose of this study was to analyze the effect of product quality, price, location on purchasing decisions and consumer satisfaction in purchasing ole-ole products at the Aku Sikka store. Data was collected by filling out questionnaires with a non-probability sampling technique using the accidental sampling method. The data were analyzed using structural equation modelling. The results of the PLS Structural Equation Model (SEM) analysis to examine the effect of product quality, price, and location variables on purchasing decisions and consumer satisfaction show that there is a positive and significant influence on product quality, price, and location variables on purchasing decisions and consumer satisfaction.